Chinese English as a Foreign Language Learners’ Individual Differences and Their Willingness to Communicate - Cheng, Ling; Xu, Jieping (Frontiers in Psychology, 2022)
One of the most significant issues in the success of language students is communication skills. Due to the high importance of the Willingness to Communicate in foreign language learning, many researchers are looking for effective factors in raising the level of communication among language learners. Reviewing the literature, the researchers explored the role of language learners’ gender, major, age, and proficiency level in their Willingness to Communicate. To gather the necessary data, the researcher administered a Willingness to Communicate questionnaire among 860 Chinese EFL students. The results of data analyses demonstrated that gender, major, and age played a significant role in determining language learners’ Willingness to Communicate. However, the findings showed that learners’ willingness to communicate could be different in all proficiency levels. The results showed that taking into account factors such as students’ gender, background, ‌and age directly helps to improve the Willingness to Communicate among language learners. Finally, solutions to improve the Willingness to Communicate are provided.